2013
DOI: 10.1021/bc300585h
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Cytotoxicity of Drug–Peptide Conjugates Regulated by Conjugation Site

Abstract: Conjugation of anticancer drugs to hydrophilic peptides such as Tat is a widely adopted strategy to improve the drug’s solubility, cellular uptake and potency against cancerous cells. Here we report that attachment of an anticancer drug doxorubicin to the N- or C-terminal of the Tat peptide can have a significant impact on their cellular uptake, cytotoxicity against both drug-sensitive and drug-resistant cancer cells. We observed higher cellular uptake by both cell lines for C-terminal conjugate relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 67 publications
5
83
0
1
Order By: Relevance
“…Although, cationic amino acids cannot self-assemble due to the repletion of their high charge, they are known for their cell penetrating abilities. One of the most popular examples of cell-penetrating peptides (CPPs), transactivator of transcription (TAT), has been widely used for anti-cancer drug conjugates to increase cellular uptake and intracellular retention in cervical cancer cells [86,87]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Although, cationic amino acids cannot self-assemble due to the repletion of their high charge, they are known for their cell penetrating abilities. One of the most popular examples of cell-penetrating peptides (CPPs), transactivator of transcription (TAT), has been widely used for anti-cancer drug conjugates to increase cellular uptake and intracellular retention in cervical cancer cells [86,87]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Furthermore, with the cargo carrying properties of CPPs, they are finding use in the delivery of cancer drugs such as doxorubicin [248,355], taxol [356], paclitaxel [357], docetaxel [358]. Using peptide conjugates for drug delivery into the cell has been a topic of interest and there are many anticancer [359], antiinflammatory [360] and neurodegenerative [361] peptide conjugate drugs that are in clinical use or under investigation. Our group has also been focusing on combining the inhibitory properties of inhibitor peptides with CPPs [362].…”
Section: Future Perspectives: Characterizing Membrane Active Peptidesmentioning
confidence: 99%
“…10 For example, the Cui laboratory has explored the pathway of DA cellular internalization. 99 With confocal microscopy, the lab has explored the pathway for free doxorubicin (DOX), as well as for DOX conjugated to the TAT peptide. As previously discussed, the TAT peptide sequence has been shown to translocate the membrane and accumulate in the cell nucleus.…”
Section: Interactions With Membranesmentioning
confidence: 99%
“…Experiments have suggested that conjugation of the TAT sequence to DOX changes the mechanism of cellular internalization from a passive mechanism to an active or endocytosis-mediated mechanism. 99 Several questions are raised by this result, such as: i) what is the change in the binding free energy of TAT with the membrane when attaching a hydrophobic drug? Additionally, ii) why does the original mechanism of cooperative pore-formation for TAT translocation become inefficient?…”
Section: Interactions With Membranesmentioning
confidence: 99%